Seasonal and interannual variability of the hydrological fronts in the Southern Ocean - Artamonov, Yu. V.; Skripaleva, E. A.; Babiy, M. V.; Galkovska, L. K. (Ukrainian Antarctic Journal, 2009)
The seasonal and interannual variability of the large-scale fronts in the Southern Ocean are investigated, based on SST satellite observations from archive AVHRR Ocean Pathfinder Data JPL NOAA/NASA during 1985-2002 and NCEP SST data during 1981-2008. It is shown, that the main frontal sections are circumpolar and most sharply shown in boundary layers adjacent to continents. Most intensive are the Southern subtropical, Subantarctical and Antarctic polar fronts. These fronts are characterized by the greatest seasonal variability of intensity with the prevailing annual signal. In the each separate basin the distinctive features connected with the region’s orography and hydrometeorological conditions are observed. The essential interannual variations of SST field in the main fronts zones are discovered.